1992
DOI: 10.1021/j100201a031
|View full text |Cite
|
Sign up to set email alerts
|

Conformational stability and force field of short-chain linear chlorophosphazenes: MNDO calculations, phosphorus-31 NMR, vibrational spectra, and normal coordinate analyses of Cl3PN(PCl2N)nP(O)Cl2 and [Cl3PN(PCl2N)nPCl3][PCl6] (n = 1, 2)

Abstract: The Raman spectra of C13PN(PC12N),P(0)C12 and [C13PN(PC12N),PC13]+Pc16-(n = 1,2) were recorded in the solid and liquid states at different temperatures. The qualitative depolarization ratios were obtained in the liquid phase. A 3rP NMR study for the molecular compounds showed a coalescence phenomenon near 220 K. The potential energy around the PN bonds for the Cl3PN(PCl2N)P(O)CI2 molecule and [C13PN(PC12N)2PC13]t cation are derived from MNDO (modified neglect of diatomic overlap) calculations. The stable confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…(5) These calculations for isolated linear phosphazenes and halophosphazenes with up to eight repeat units show that the twisted backbone structure is more stable than the planar trans−cis structure. This finding disagrees with many other calculations reported in the literature, which were mostly limited optimizations done with a planarity constraint. The accuracy level of computational methods is probably another source of the disagreement.…”
Section: Summary and Remarkscontrasting
confidence: 99%
See 2 more Smart Citations
“…(5) These calculations for isolated linear phosphazenes and halophosphazenes with up to eight repeat units show that the twisted backbone structure is more stable than the planar trans−cis structure. This finding disagrees with many other calculations reported in the literature, which were mostly limited optimizations done with a planarity constraint. The accuracy level of computational methods is probably another source of the disagreement.…”
Section: Summary and Remarkscontrasting
confidence: 99%
“…The primary goal of the present study is to extend our understanding of molecular structures and conformational properties of polyphosphazenes by performing high level theoretical calculations. So far, computational studies reported in the literature are based on empirical, semiempirical, and low level ab initio methods . This may be partly responsible for the controversial results obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting observation from the Raman spectra of the 14 N-MEEP and 15 N-MEEP is that there were no obvious differences. This leads to the conclusion that many of the expected vibrations associated with P-N bonding as identified with model compounds [33][34][35][36] do not appear to be Raman active, at least not in MEEP, and the spectrum is dominated by the vibrational modes of the side chains. The only difference found in the spectra that could be associated with P-N bonding was found in the peak at 625 cm -1 which is apparently a combination of a P-N bending mode 34,36 and a P-O mode.…”
Section: Resultsmentioning
confidence: 99%
“…Polyphosphazenes have drawn considerable interest as technologically valuable, new polymeric materials because various kinds of poly(organophosphazenes) can be easily prepared from a single polyphosphazene, the poly(dichlorophosphazene), by the macromolecular substitution reaction with nucleophiles such as alkoxides and primary amines, and their properties can be widely tuned by proper selection of the introducing substituents , and computational calculations based on empirical, semiempirical, and the ab initio method, 3e,, there are controversies about these results, and both the helical 2,4 and cis − trans planar 3,5 conformations have been proposed for the polyphosphazenes. Moreover, a large number of polyphosphazenes bearing optically active side groups, such as amino acid esters and steroidal and glucosyl groups, have been prepared in order to develop biomedical materials because they are bioerodible, but their conformations have not yet been discussed in detail …”
mentioning
confidence: 99%